Peran Muzakki Terhadap Intensi Zakat Profesi Kota Surabaya - Ratih Fitrianingtyas; Zubaidah Nasution (Universitas Muhammadiyah Surabaya, 2019)
AbstractThis research aims to determine intention of muzakki to pay the professional zakat. The population in this research is Muslim workers inSurabaya. The total of respondents as the research population is 134workers. Techniques used in sampling are non probability sampling withpurposive sampling technique. This research used primary data collectedthrough questionnaires distributed to respondents based on researchinstruments. The data obtained were then analyzed using regressionanalysis. Based on the result of hypothesis testing show that religiosity has asignificant positive effect on muzakki intentions and income has a positive butnot significant effect on muzakki intentions. This means that the higher thereligiosity possessed by muslim workers, the higher the intention of muzakkito pay zakat. Keywords : Religiosity, Income, The Professional Zakat, Intention of Muzakki.